Arbuscular Mycorrhizae Mitigate Aluminum Toxicity and Regulate Proline Metabolism in Plants Grown in Acidic Soil - Modhi O. Alotaibi; Ahmed M. Saleh; Renato L. Sobrinho; Mohamed S. Sheteiwy; Ahmed M. El-Sawah; Afrah E. Mohammed; Hamada Abd Elgawad (Journal of Fungi, 2021)
Arbuscular mycorrhizal fungi (AMF) can promote plant growth and induce stress tolerance. Proline is reported to accumulate in mycorrhizal plants under stressful conditions, such as aluminum (Al) stress. However, the detailed changes induced in proline metabolism under AMF–plant symbiosis has not been studied. Accordingly, this work aimed to study how Al-stressed grass (barley) and legume (lotus) species respond to AMF inoculation at growth and biochemical levels. The associated changes in Al uptake and accumulation, the rate of photosynthesis, and the key enzymes and metabolites involved in proline biosynthesis and degradation pathways were studied. Soil contamination with Al induced Al accumulation in tissues of both species and, consequently, reduced plant growth and the rate of photosynthesis, while more tolerance was noticed in lotus. Inoculation with AMF significantly reduced Al accumulation and mitigated the negative impacts of Al on growth and photosynthesis in both species; however, these positive effects were more pronounced in barley plants. The mitigating action of AMF was associated with upregulation of proline biosynthesis through glutamate and ornithine pathways, more in lotus than in barley, and repression of its catabolism. The increased proline level in lotus was consistent with improved N metabolism (N level and nitrate reductase). Overall, this study suggests the role of AMF in mitigating Al stress, where regulation of proline metabolism is a worthy mechanism underlying this mitigating action.